Structural and phase transitions in nanocluster ethanol samples at low temperatures - Efimov, V.; Izotov, A.; Mezhov-Deglin, L.; Nesvizhevskii, V.; Rybchenko, O.; Zimin, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
Results of neutron (SANS study) and x-ray diffraction experiments with nanocluster samples of deutero-ethanol (C2D5OD) or ordinary pure ethanol (C2H5OH) are presented. A deuterated ethanol sample, formed via quick cooling of ethanol–helium mixture down to 1.6 K, had clusters with the size of d ~ 20–30 nm at liquid helium temperatures. After warming up to liquid nitrogen temperatures the gel decays into an amorphous white powder. It was observed that these powder samples remained in the amorphous state even after keeping at T ≤ 90 K for a long time (a few months). The neutron studies were supported by further x-ray investigations of the structure and the phase transitions in the highly dispersed powder samples, which were created via the decay of the gel samples of ordinary ethanol at temperatures above liquid nitrogen up to 150 K at saturated nitrogen gas pressure. Annealing of the “gel” sample during half an hour at a temperature of T ~ 110 K resulted in a phase transition to a monoclinic phase with the crystallite sizes ~30–40 nm. For comparison we studied the structure and phase transitions in “bulk” samples, prepared via quick freezing of liquid ethanol down to liquid nitrogen temperature. The “bulk” sample had a similar transition at T ~ 125 K, which is by 15 K higher than the temperature of the intensive phase transition in the “gel” sample. The mean grain size in the bulk material was d ≥ 60 nm.